A tale of two worlds: contrasting realities in southern and northern Zambia during El Niño - Kudzanai Chimhanda (International Maize and Wheat Improvement Center, 2024)
El Niño has contributed to starkly different weather patterns in northern and southern Zambia. On World Water Day 2024, this piece navigates the complex challenge of mitigating water abundancy and scarcity through different agricultural practices that support livelihoods and food security.